High‐Pressure CO Electroreduction at Silver Produces Ethanol and Propanol. (24th August 2021) - Raaijman, Stefan J.; Schellekens, Maarten P.; Corbett, Paul J.; Koper, Marc T. M.
Abstract: Reducing CO2 to long‐chain carbon products is attractive considering such products are typically more valuable than shorter ones. However, the best electrocatalyst for making such products from CO2, copper, lacks selectivity. By studying alternate C2+ producing catalysts we can increase our mechanistic understanding, which is beneficial for improving catalyst performance. Therefore, we investigate CO reduction on silver, as density functional theory (DFT) results predict it to be good at forming ethanol. To address the current disagreement between DFT and experimental results (ethanol vs. no ethanol), we investigated CO reduction at higher surface coverage (by increasing pressure) to ascertain if desorption effects can explain the discrepancy. In terms of product trends, our results agree with the DFT‐proposed acetaldehyde‐like intermediate, yielding ethanol and propanol as C2+ products—making the CO2 electrochemistry of silver very similar to that of copper at sufficiently high coverage. Abstract : Reducing CO2 to long‐chain carbon products is of great interest. Here, CO reduction was studied on silver at high surface coverage, as DFT results predict it to be good at forming ethanol. The results agree with the DFT‐proposed acetaldehyde‐like intermediate, yielding ethanol, ethylene glycol and propanol as C2+ products—making the CO2 electrochemistry of silver very similar to that of copper at sufficiently high coverage.